Brisingr, or, The seven promises of Eragon Shadeslayer and Saphira Bjartskular [compact disc, unabridged] - Paolini, Christopher (Paolini, Christopher. Inheritance (Random House Audio Publishing), 2008)
Continuing the story of Eragon and Eldest, Christopher Paolini delivers another action-packed installment. Eragon, the Dragon Rider, and his mount Saphira barely managed to survive the battle of the Burning Plains. Now he must decide what comes next, when it seems that all of his allies are in need of his services.